Using Pulmozyme DNase Treatment in Lentiviral Vector Production - Shaw, Aaron (Mary Ann Liebert, Inc., 2012)
In the production of lentiviral vector for clinical studies the purity of the final product is of vital importance. To remove plasmid and producer cell line DNA, investigators have incubated the vector product with Benzonase, a bacterially derived DNase. As an alternative we investigated the use of Pulmozyme, a U.S. Food and Drug Administration-approved human DNase for the treatment of cystic fibrosis, by comparing the efficiency of DNA removal from lentiviral vector preparations. A green fluorescent protein-expressing lentiviral vector was prepared by transient calcium phosphate transfection of HEK 293T cells and DNA removal was compared when treating vector after harvest or immediately after transfection. The effectiveness of DNase treatment was measured by quantitative PCR using primers for vesicular stomatitis virus glycoprotein G viral envelope plasmid. When treating the final product, 1-hr incubations (37°C) with Pulmozyme at 20 U/ml reduced plasmid DNA to undetectable levels. Longer incubations (up to 4 hr) did not improve DNA removal at lower concentrations and the effectiveness was equivalent to or better than Benzonase at 50 U/ml. Attempting to use Pulmozyme immediately after transfection, but before final medium change, as a means to decrease Pulmozyme concentration in the final product provided a 2-log reduction in DNA but was inferior to treatment at the end of production. Pulmozyme, at concentrations up to 100 U/ml, had no measurable effect on infectious titer of the final vector product. The use of Pulmozyme is likely to increase the cost of DNase treatment when preparing vector product and should be considered when generating clinical-grade vector products.